Pemetaan Bahaya Tingkat Tsunami Untuk Penentuan Titik Shelter serta Jalur Evakuasi Sebagai Upaya Mitigasi Ancaman Tsunami Megatrust Menggunakan Penginderaan Jauh dan Sistem Informasi Geografis di Pesisir Kabupaten Tasikmalaya: Indonesia - Valgunadi, Ade Novit (Universitas Negeri Surabaya, 2024)
The threat of megathrust, which has the potential to cause a tsunami with waves as high as 34 meters on the coast of South Java, is undoubtedly worrying and must be mitigated as best as possible. This research aims to map the tsunami hazard with locations in Tasikmalaya Regency. The method used in this research is remote sensing and geographic information systems with quantitative descriptive analysis techniques. The data used are land use, distance from the coastline, distance from the river line, slope, and land elevation. The results of this research show that the coast of Tasikmalaya Regency, based on five parameters, namely elevation, slope, distance from the beach, distance from the river, and land use, has a high level of danger and for disaster mitigation ten temporary shelter points have been produced which are distributed along the coast of Tasikmalaya Regency. This research also produces an evacuation route to the temporary shelter point created, and an estimated road 1.8 km from the temporary shelter can be reached in 20 minutes on foot.